2013
DOI: 10.1016/j.jcrs.2012.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of +3.00 D and +4.00 D near addition on functional outcomes of a refractive multifocal intraocular lens model

Abstract: Compared with the +4.00 D add, the +3.00 D near add gave better intermediate results in the defocus curve without compromising distance or near visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…This finding was reported some years ago by Petermeier et al 20 in a clinical study aimed at comparing apodised diffractive IOLs with different levels of addition. Also Rabsilber et al 21 showed a better intermediate visual acuity for the lower near addition in the comparison of +4.0 D and +3.0 D refractive MIOLs.…”
Section: Discussionmentioning
confidence: 88%
“…This finding was reported some years ago by Petermeier et al 20 in a clinical study aimed at comparing apodised diffractive IOLs with different levels of addition. Also Rabsilber et al 21 showed a better intermediate visual acuity for the lower near addition in the comparison of +4.0 D and +3.0 D refractive MIOLs.…”
Section: Discussionmentioning
confidence: 88%
“…; Rabsilber et al. ). The present study, however, suggests that combined implantation of diffractive MIOLs with +3D and +4D addition power provides better binocular near vision than bilateral implantation of the same +3D MIOLs, probably due to binocular summation.…”
Section: Discussionmentioning
confidence: 96%
“…Intermediate vision is a challenge with multifocal IOLs, and especially in computer reading [16]. IOLs with a +4dpt add have an optimal reading distance of about 30 cm that might be too close, and visual acuity at 50-70 cm may be as low as 0.4 logMAR ( fig.…”
Section: Intermediate Vision With Multifocal Intraocular Lensesmentioning
confidence: 99%